Erasing Rural Massachusetts: Consolidation and the Urban Revolution in Education - Cervone, Jason A (Australian and International Journal of Rural Education, 2019)
Massachusetts is the least rural state in the US, and its existing rural communities are shrinking. This paper examines the historical processes of urbanization, specifically through industrialization that have come to dominate and erase rural communities in the state. The capitalist mindset behind industrialization has spread to education where the state has a long history of pursuing consolidation as a way to deal with the supposed problems of rural schools. This policy represents a narrow viewpoint of what education should be and does not value the lived experiences of rural youth. These phenomena are analyzed using Henri Lefebvre's Urban Revolution in an effort to theorize the way education policy is being used by the state to increase urbanization and erase rural schools and communities.